Intercultural workplace relationships in the hospitality industry: Beyond the tip of the iceberg. (February 2017) - Vassou, Chrystalla; Zopiatis, Anastasios; Theocharous, Antonis L.
Highlights: Workplace diversity is viewed through the lens of the contact hypothesis. SEM and mediation analysis are used to test the proposed relationships. Contact with foreign colleagues influences wider attitudes towards foreigners. Intercultural contact indirectly influences affective commitment via fair treatment. The industry should demonstrate belief in diversity and implement relevant practices. Abstract: The impact of intercultural workplace relationships on local employees has been scarcely investigated in hospitality. This paper adopts the contact hypothesis perspective in order to explore the ways in which intercultural encounters between foreign and local hospitality employees influence the latter, in sociocultural and organizational terms. A conceptual model is developed, tested within the Cypriot hospitality industry, and analyzed using structural equation modeling. Findings support the contact hypothesis, in that prior attitudes towards the ethnically different "other" influence the development of intercultural workplace relationships, which in turn influence local employees' wider attitudes towards foreigners. Furthermore, the importance of fair treatment and respect at work are stressed, as they mediate the relationship between intercultural workplace relationships and affective commitment. Implications for hospitality organizations are derived and suggestions are provided.